Mapping of Drebrin Binding Site on F-Actin - Grintsevich, Elena E. (2010)
Drebrin is a filament binding protein involved in organizing the dendritic pool of actin. Previous in vivo studies identified the actin-binding domain of drebrin (DrABD), which causes the same rearrangements in the cytoskeleton as the full length protein. Site directed mutagenesis, electron microscopic (EM) reconstruction and chemical cross-linking combined with mass spectrometry analysis were employed here to map the DrABD binding interface on actin filaments. DrABD could be simultaneously attached to two adjacent actin protomers using the combination of 2-iminothiolane (Traut's reagent) and 1,1-methanediyl bis(methanethiosulfonate) (MTS1). Site directed mutagenesis combined with chemical cross-linking revealed that residue 238 of DrABD is located within 5.4 Å from C374 of actin protomer 1, and drebrin's native cysteine 308 is in close proximity to C374 of actin protomer 2. Mass spectrometry analysis revealed that a zero length cross-linker, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC), can link the N-terminal G-S extension of the recombinant DrABD, to E99 and/or E100 on actin. Efficient cross-linking of drebrin residues 238, 248, 252, 270, and 271 to actin residue 51 was achieved with reagents of different length (5.4 – 19 Å). These results suggest that the ‘core’ DrABD is centered on actin's subdomain 2 and may adopt a folded conformation upon binding to F-actin. The results of EM reconstruction, which are in a good agreement with the cross-linking data, revealed polymorphism in DrABD binding to F-actin and suggested the existence of two binding sites. These results provide new structural insight into the previously observed competition between drebrin and several other F-actin binding proteins.